Esthetic Dentistry - Abdulwahab, Ahmed; Aljobory, Ali; Apkhadze, Giorgi; Dzodzuashvili, Grigol (Caucasus Journal of Health Sciences and Public Health, 2016)
A smile is a contagious thing. Give to the world and the world will give back to you. Smile at the world and the world will smile back at you. You will brighten the days of those around and make a difference in their lives… simply by smiling! Exist some ways how we can enhance patients smile. It’s very important patients involvement during creating of their smile because exist statistic information by Zuhre Zafersoy Akarslan, Burak Sadik, Hulya Erten, Erdem Karabulut (Hacettepe University of Medicine, Ankara, Turkey ). According to the analyses of the verifying data, 55.1% of the patients were dissatisfied with the color of their teeth, 42.7% with dental appearance, 23.3% were hiding teeth while smiling, 16.1% had non-esthetic restorations and 11.9% thought that their anterior teeth were protruding. Esthetic restoration was found to be the most-performed treatment recently (29.0%) and whitening of teeth was the most-desired dental treatment (49.0%). Gender, age and education level had an effect on satisfaction and received previous and desired dental treatments for improvement of esthetic. Exist some ways how we can enhance patients smile. DSD - we can choose desired shade color form location and teeth visibility degree during smile we can show digital version of final restoration to patient DSD esthetically involves the patients in the restorative or smile enhancement process, making them the codesigner of their own treatment by sharing objectives, expressing their desires and expectations with the restorative team. The interaction between patient and dental specialist is improved by photos and videos taken at several steps of the treatment. Anteriores – patient can choose tooth design from special catalogue. Whitening is the most common esthetic dental procedure. There are many whitening options are now available. For example Laser whitening technique in which gums are covered with rubber and a bleaching chemical is applied on the teeth. Veneers are ultra-thin, custommade porcelain laminates that are bonded directly to the teeth. They are an option for closing gaps, enhance the shape, or change the color of teeth that do not respond well to whitening procedures. In the majority of the cases, some level of tooth reduction is necessary for optimal results. Full crowns – metal ceramic , all ceramic (Hot press ceramic, E-Max ceramic), zirconium ceramic. Gum lift is aesthetic dental procedure that raises and sculpts the gum line. The procedure involves reshaping the tissue and/or underlying bones to create the appearance of longer or more symmetrical teeth. In older patient we can enhance there esthetic by RDP. Press-ceramic offers excellent fit, form and function combined with high strength of 400 MPa. The material is supplied in four levels of translucency and two sizes. The resulting restorations exhibit lifelike esthetics, independent of the shade of the preparations. Press ceramic is used to produce singletooth restorations, bridges for the anterior and premolar region and implant superstructures.